The most beautiful part of your body is where it’s headed: T4t togetherness in Jules Fischer’s performance Vanitas - Møller Madsen, Storm (Peripeti, 2024)
This article analyses the performance and total installation Vanitas (the musical) (2022) by the Danish choreographer and visual artist Jules Fischer. Through a t4t methodology and anchored in my own embodied and affective experience as a trans person I argue that Vanitas offers a knowing trans togetherness we who are trans can experience and feel in different ways than those who do not have such experiences. Vanitas centers trans experience and togetherness not by explaining what transness is, but by offering a performative space filled with ambivalence, embodied practicing and an alongsided togetherness. A temporary t4t (trans-for-trans) togetherness shaped around the multiplicity of ways, we as trans people, together and alongside one another, move closer to each other and ourselves in an effort to heal, survive and even thrive. Denne artikel analyserer performancen og totalinstallationen Vanitas (the musical) (2022) af den danske koreograf og billedkunstner Jules Fischer. Gennem en t4t-metodologi og forankret i min egen kropslige og affektive oplevelse som transperson argumenterer jeg for, at Vanitas tilbyder et vidende transfællesskab, vi, der er transpersoner, kan opleve og mærke på andre måder end dem, der ikke har disse erfaringer. Vanitas centrerer transoplevelse og -fællesskab, ikke ved at forklare, hvad transhed er, men ved at tilbyde et performativt rum fyldt med kropslig gøren og ambivalente fællesskaber. Vanitas skaber et midlertidigt t4t (trans-for-trans) fællesskab omkring den mangfoldighed af måder, hvorpå vi som transpersoner, sammen og side-om-side, bevæger os tættere på hinanden og os selv i et forsøg på at overleve og hele.